Comparative analysis of the exergy efficiency of methods for protecting gas exhaust ducts of boiler plants - Fialko, Nataliia; Stepanova, Alla; Navrodska, Raisa; Shevchuk, Svitlana (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports the results of studying the exergy effectiveness of thermal methods for anti-corrosion protection of the gas-draining tracts of boiler plants. These include the method of mixing heated air into flue gases, the method of passing part of the hot gases of the boiler through the bypass chimney, and a flue gas drying method. The research involved the devised comprehensive procedure based on an exergy approach. The dependences of exergy loss Elos and the heat- exergy criterion ε on the following parameters of thermal methods have been established: the amount of heated air N mixed into flue gases, the proportion of bypassed flue gases K, and the amount of dried flue gases R. A comparative analysis of the effectiveness of heat recovery systems when applying the methods considered has been performed. It has been established that for the method of mixing, Elos and ε at ambient temperature ten=10 °C demonstrate the lowest values, that is, the efficiency of the system, in this case, is the highest. The most effective, when implementing the bypass method, is the heat recovery system at ten=10 °C. Under the method of drying, at all values of the amount of dried flue gases, the loss of exergy is the lowest at ten=0 °C. As regards the heat- exergy criterion, at values R≤20 %, the lowest values of ε are observed at ten=10 °C. At R>20 %, the lowest values of ε are at ten=0 °C. Thus, the efficiency of the system when implementing the method of drying is the highest at ten=0 °C and at the amount of dried air of R>20 %. The study reported here would provide the necessary information for designing optimal heat recovery schemes. The development of this study is to establish the relationship between the exergy and environmental efficiency of thermal protection methods in order to further reduce toxic emissions.